2020
DOI: 10.1002/admi.202000578
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Tunable Printed Bifocal Liquid Crystal Microlens Arrays

Abstract: In this communication, the fabrication of electrically tunable bifocal liquid crystal (LC) microlenses using drop‐on‐demand inkjet printing is demonstrated. By treating the glass substrate with a homeotropic alignment layer, the printed droplets are found to form plano‐convex lenses with focal lengths in the range of 220–463 µm, depending upon the number of droplets deposited at each location on the substrate. The precision of the process allows for the microlenses to be deposited in between in‐plane indium ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…For example, in 2020, S. M. Morris et al reported LCMs by using a DoD inkjet printing system. [ 48 ] As shown in Figure 6b. I, the high‐precision needle controlled by pulse signal can extricate LC droplets with an accuracy of ±5 µm.…”
Section: Fabricationsmentioning
confidence: 96%
See 3 more Smart Citations
“…For example, in 2020, S. M. Morris et al reported LCMs by using a DoD inkjet printing system. [ 48 ] As shown in Figure 6b. I, the high‐precision needle controlled by pulse signal can extricate LC droplets with an accuracy of ±5 µm.…”
Section: Fabricationsmentioning
confidence: 96%
“…Reproduced with permission. [ 48 ] Copyright 2020, Wiley‐VCH. h) The polymer mold fabricated by TPP direct‐laser writing.…”
Section: Design Principlesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, printing has already been employed with LC materials to develop monodisperse LC solutions, and optically-pumped thin-film lasers, as well as electrically and thermally tunable microlenses. [36][37][38][39] Due to its versatility, DoD inkjet printing offers a unique platform for the manufacture of PDLC films. By printing an LC and UV-curable polymer ink, PDLC films with spatially patterned emblems and logos can be successfully manufactured.…”
Section: Introductionmentioning
confidence: 99%